GEMAR CETING ( GERAKAN MAHASISWA DAN REMAJA CEGAH STUNTING) DENGAN PERMAINAN SETATAK - Julita, Sety; Bahri, Aisyah Amanda; Hardita, Lisha Febrianty; Rifani, Putri Ardila; Sari, Maya (PITIMAS: Journal of Community Engagement in Health, 2023)
Stunting is a health problem that must be of particular concern to all sectors. Stunting is a condition of failure to thrive in toddlers due to chronic malnutrition that occurs since the baby is in the womb so that the child is shorter than his age and will appear after the child is 2 years old. Prevention of stunting must be done early, because it can affect the growth and development of children. Young women have a role in controlling stunting reduction in accordance with Presidential Decree No. 72 of 2021 Chapter 2 Article 3 implementation of accelerated reduction of stunting with the main target group being teenagers. The community service student creativity program (PKM-M) involves 25 grade 9 girls at SMPN 1 Rengat Barat as targets and are expected to become agents of change in stunting control. . From this activity it was found that the level of knowledge of young women increased as seen from the results of the post test scores which were higher than the pre test. This activity ran smoothly according to the goals